Genetic parameters in okra - Paiva, Waldelice Oliveira de; Costa, Cyro Paulino da (Pesquisa Agropecuaria Brasileira, 1998)
Environmental factors induce several interactions in okra (Abelmoschus esculentus (L.) Moench), resulting in plant modifications both on the vegetative and reproductive phase. Environment can also cause variation in values of some genetic parameters. In order to estimate the genetic variability and some genetic parameters and to study the correlations among some yield characters eleven okra cultivars were evaluated in two seasons (winter and summer), during two years. The experimental design used was a randomized block, with five replications. There was enough genetic variability among cultivars for all the studied characters. Estimated heritabilities showed high values for fruit length, diameter and weight, plant height and number of branches per plant. High correlation coefficients observed for height of first fruiting node and plant height, number of fruits and yield and earliness and yield, demonstrate the possibility of the development of early, short and high-yielding cultivar. The lowest heritability to the easily measurable characters and the highest values of cultivar x environment interaction for all the studied characters except fruit length and average weight suggests that okra breeding programs must employ methods that assure a good environmental control.